Dissolving Microneedle Patch for Transdermal Delivery of Human Growth Hormone - Lee, Jeong Woo (2011)
Clinical impact of biotechnology has been constrained by the limitations of traditional hypodermic injection of biopharmaceuticals. Microneedle patches have been proposed as a minimally invasive alternative. In this study, we assess the translation of a dissolving microneedle patch designed for simple, painless self-administration of biopharmacetucials that generates no sharp biohazardous waste. To study pharmacokinetics and safety of this approach, human growth hormone (hGH) was encapsulated in 600 μm long dissolving microneedles composed of carboxymethylcellulose and trehalose using an aqueous, moderate-temperature process that maintained complete hGH activity after encapsulation and retained most activity after storage for up to 15 months at room temperature and humidity. After manual insertion into the skin of hairless rats, hGH pharmacokinetics were similar to conventional subcutaneous injection. After patch removal, the microneedles had almost completely dissolved, leaving behind only blunt stubs. The dissolving microneedle patch was well tolerated, causing only slight, transient erythema. This study suggests that a dissolving microneedle patch can deliver hGH and other biopharmaceuticals in a manner suitable for self-administration without sharp biohazardous waste.